Manipulation analysis of two cooperating arms - Ferreira, N. M. Fonseca (2019)
Many tasks involving manipulation require cooperation between robots. Meanwhile, it is necessary to determinate the adequate values for the robot parametrs to obtain a good performance. This paper discusses several aspects related with the manipulability and the workspace of two co-operative robots when handling objects with different lengths and orientations.